Infrared image enhancement and human detection performance measures. (16th June 2010) - Hanton, K.; Sunde, J.; Butavicius, M.; Gluscevic, V.
The ability to detect and recognise dangerous objects at a safe distance is a very important task in a number of defence, police and security applications. In this paper, we look at ways of increasing the effectiveness of infrared imagery for object recognition through processes such as super-resolution image reconstruction and deconvolution methods. In this paper, we propose two techniques for assessing image quality improvement: operator assessment and edge detection; and report on some initial work recently undertaken.